David and the giant - Little, Emily; Wilhelm, Hans (New York : Random House, 2003)
A simple retelling of the Old Testament story of the shepherd boy, David, whose faith in God helped him overcome the Philistine giant Goliath.
Originally published: New York : Random House, c1987.
Keywords: David; Goliath; David; Goliath; Bible stories, English; Bible stories